Profit taxation and finance constraints - Christian Keuschnigg; Evelyn Ribi (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the absence of financing frictions, profit taxes reduce investment by their effect on the user cost of capital. With finance constraints due to moral hazard, investment becomes sensitive to cash-flow and own equity of firms. We propose a corporate finance model of investment and derive three central results: (i) Even small taxes impose first order welfare losses on financially constrained firms; (ii) ACE and cashflow tax systems, which are investment neutral in the neoclassical model, are no longer neutral when firms are finance constrained. (iii) When banks are active and provide external finance together with monitoring services, the two systems not only reduce investment, but are also no longer equivalent. With active banks, investment is subject to double moral hazard and the timing of tax payments becomes important. The ACE system gives tax relief at the return stage and provides better incentives than a cash-flow tax which gives tax relief upfront.
Keywords: G38; H25; 330; finance constraints; profit tax; cash-flow tax; ACE tax